Inserção socioprofissional de jovens do campo: desafios e possibilidades de egressos da Escola Família Agrícola Bontempo - Marinalva Jardim Franca Begnami (2010)
This study aimed to analyze the socio-professional integration of young people from the rural areas, graduates from the Escola Família Agrícola Bontempo, located on Jequitinhonha valley, Minas Gerais. The EFA Bontempo, established in 2000, works through the alternationpedagogy, regular mode of education developed in Brazil for over fifty years. The EFA Bontempo was the first in Minas Gerais to offer technical courses in High School, whose primary audience was agriculturists sons from Jequitinhonha Valley. It was tried to identify and to analyze the challenges and opportunities experienced by the graduates during the insertion in the productive, social, political and cultural spaces. For this purpose, the research focused on the professional project built during the school formative path, which was also considered the centerline to the inclusion of these young people. The approaches adopted were qualitative and quantitative, as it was understood that they are interconnected and essential to understand the study object. Among the sources of data collection, it was necessary to resort to desk research,questionnaire and semi-structured interviews. From the universe of 146 graduates, on the period from 2003 to 2006, 128 questionaries were sent, and from these 90 gave return to the research.The analysis of the data collected through questionnaires reveals that among ninetygraduates participants, 59 were male and 31 were female. They are aged between 19 and 42 years, mostly between 21 and 26 years old, both men and women. Among them, 85% are single, and, among the married graduates, men are the majority. The choice of graduates for studying atEFA Bontempo was primarily due to the fact that it is a school which offers High School and technical courses. It was found that 39% of the graduates attended or are attending college. This phenomenon shows that, overcoming the tendency of a bigger access of young people to Higher Education, especially nowadays, schooling extension is related to the lack of employment, which also occurs in the rural areas. Although a minority of graduates has put their professional projects into practice, most tried and failed it, and most of them would like to practice it. Thestudy shows that the themes choice of the projects is related to families activities, mostly in the agricultural production area. The challenge presented by the students to implement their projects, among others, was the access to land and credit, especially to Pronaf Jovem. The data show that, directly or indirectly, the alternation pedagogy formation helped to improve social participation of young people, since 89% of them participate in social activities in their communities. The activities of family agriculture, commerce, education, social organization, and union and social movements are the biggest areas of employability of these graduates. It was found that 63% of them are in occupations which are consistent with their professional formation. However, 98% of them want to insert in their formation field. The analysis of this phenomenon shows the importance, for rural youth, of having the opportunity to accessprofessional formation and work, which are essential conditions to exercise the right of being free to leave the rural areas, and more specifically Jequitinhonha Valley, by their own choice, notby lack of opportunities. Thus, in conclusion, despite the challenges faced by the rural youth who graduated from EFA Bontempo, the scenario is also of possibilities of insertion in several social, cultural and political productive spaces, in the field and in the city.